(9+3x)-3x=

Simple and best practice solution for (9+3x)-3x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9+3x)-3x= equation:


Simplifying
(9 + 3x) + -3x = 0

Remove parenthesis around (9 + 3x)
9 + 3x + -3x = 0

Combine like terms: 3x + -3x = 0
9 + 0 = 0
9 = 0

Solving
9 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x-5(x+4)=-(x-7) | | 9(x-7)+14(x+10)= | | 4(2x+12)-6x= | | 7(6x+4)+5x= | | 7(t-3)+7t=7(2t+5)-12 | | 5(2x+6)-20= | | 2x^2-32x-72=0 | | (6x+16)-6= | | (55x+60y)-(10x-22y)= | | 7(5x+12)+13x-12= | | (63x+47y)-(3x-6y)= | | 1.6q-2.5-1.5q=-0.9q-3.3 | | =(-7)*10+5*10 | | (2x-x+9x^2)/(-1+3x) | | (w^2+10w+25)(w-2)=a+70 | | -8y+4=-9y+1 | | 2(x-5)+7=17 | | 35=x^2+x | | =444444+5362664536 | | (w^2+10w+25)(w-2)=70 | | 3x-24y=-30 | | 3x^3-2x^2+12x-8=0 | | =34+45 | | -64=15-4 | | 5(2x+6)=(-5-2x)+3x | | 207(47/69)2/9 | | (9x^2+x)/(3x-1) | | x^1/2(x-6) | | -h/2+8=6 | | h/-2+8=6 | | 0.45/4.5 | | -1/5-1=12 |

Equations solver categories